Prolonged field care for traumatic extremity injuries: defining a role for biologically focused technologies - Connor P. Dolan (Nature Portfolio, 2021)
Extremity injuries occur frequently during warfare. While traditionally treated in definitive clinics, the future battlefield is projected to be different in a variety of ways, and there will likely be a shift towards prolonged field care (PFC) for treating extremity traumas. PFC is defined as field medical care that is applied beyond “doctrinal planning time-lines” by a tactical medical practitioner in order to decrease patient mortality and morbidity. At present, there is an urgent need to develop biologically focused technologies for treating extremity injuries in the PFC setting. Herein, the case is made for why rapid advancements in PFC is critical to achieve optimal care for injured Service members in the future, and important design criteria for developing next-generation biologically focused technologies. Finally, a case example—i.e., Gustilo Type III fracture—is presented to illustrate how these biologically focused technologies could be utilized to treat an extremity injury within a PFC environment.